DES GENE MUTATION IN A FAMILY OF PROBAND WITH MYOFIBRILLARY MYOPATHY AND NON-COMPACTION CARDIOMYOPATHY, RESULTED IN CARDIAC TRANSPLANTATION - R. P. Myasnikov; N. V. Shcherbakova; О. V. Kulikova; А. N. Meshkov; M. S. Kharlap; А. V. Kiseleva; А. А. Zharikova; Е. L. Dadali; N. A. Semenova; S. N. Koretsky; О. V. Blagova; Е. А. Mershina; et al. (Российский кардиологический журнал)
Aim. To perform clinical and instrumental examination and genetic testing using the method of exome sequencing of proband and his relatives of 1 and 2 degrees of kinship with myofibrillary myopathy and non-compaction cardiomyopathy.Material and methods. The object of the study: proband with non-compaction cardiomyopathy and his relatives of 1 and 2 degrees of kinship. All participants underwent clinical and instrumental examination including: blood collection for genetic testing, complete cell blood count, biochemical blood assay (levels of total protein, alanine-aminotransferase, aspartate aminotransferase, lactate dehydrogenase, bilirubin, urea, creatinine, uric acid, potassium, sodium, creatinekinase, MB-fraction of creatinekinase, brain natriuretic peptides, C-reactive protein), coagulation profile (partial thromboplastin time, thrombin clotting time, levels of antithrombin III, INR, D-dimer), ECG, Holter ECG monitoring, cardiac MRI). The non-compaction myocardium was diagnosed according to echocardiographic criteria of non-compaction myocardium. Sequencing was performed with genomic sequenator Illumina HiSeq 1500 (Illumina, USA). Genomic libraries were prepared with Kapa Library Amplification Kit (Roche, Switzerland), NimbleGen SeqCap EZ Exome v3.0 (Roche, Switzerland) were used for exome enrichment. Then bioinformatic analysis was done; variants in 188 genes associated with any cardiomyopathy development were prioritized and assessed for pathogenenity.Results. Proband was diagnosed with myofibrillar myopathy and familial form of non-compaction cardiomyopathy (according to MRI and echocardiographic criteria). Novel probably pathogenic variant was found in DES gene — c.330_338del. Other pathogenic and probably pathogenic variants were not found. Conclusion. Novel variant of DES gene c.330_338del is probably responsible for the development of myofibrillar myopathy and non-compaction cardiomyopathy.